Evolution of Latin American Higher Education Institutions’ Commitment to the 2030 Agenda - Arias Valle, Maria Belen (2025)
This study examines the evolution of Latin American higher education institutions’ (HEIs) commitment to the 2030 Agenda, using their participation in the Times Higher Education Impact Rankings (THE-IR) as a key measure. The analysis covers 2019 to 2024, assessing the growth in participating HEIs and their performance in various Sustainable Development Goals (SDGs). The primary goal is to identify trends in HEI participation in THE-IR and evaluate their adoption of SDGs. A quantitative approach, using descriptive statistics, was applied. Data were sourced from THE-IR’s official database, covering six years. Trend analysis and visualizations were conducted using specialized statistical tools. The findings indicate a steady increase in HEI participation, with strong results in Brazil, Chile, Colombia, and Mexico. The most frequently adopted SDGs include Good Health and Well-being (SDG 3), Quality Education (SDG 4), and Affordable and Clean Energy (SDG 7). While the commitment of Latin American HEIs to the 2030 Agenda is growing, it remains in the early stages. There is a clear need for greater institutional support and government policies to advance sustainability in education.